2015
DOI: 10.5114/pdia.2015.48729
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Helicobacter pylori and idiopathic chronic urticaria: effectiveness of Helicobacter pylori eradication

Abstract: IntroductionChronic urticaria (CU) is defined as the presence of urticaria on most days of the week for a period of 6 weeks or longer. Some studies have reported an association between CU and Helicobacter pylori (H. pylori) infection.AimTo determine the prevalence of H. pylori infection using the stool antigen test in patients with idiopathic CU and to investigate the infected patients with CU following eradication of H. pylori.Material and methodsOne hundred patients with idiopathic CU and 100 healthy control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 38 publications
4
16
0
2
Order By: Relevance
“…Concerning dermatological diseases, Mogaddam et al. reported a positive association between H. pylori and chronic urticaria, while other authors showed a possible association with rosacea and vitiligo .…”
Section: Miscellaneousmentioning
confidence: 98%
“…Concerning dermatological diseases, Mogaddam et al. reported a positive association between H. pylori and chronic urticaria, while other authors showed a possible association with rosacea and vitiligo .…”
Section: Miscellaneousmentioning
confidence: 98%
“…In recent years, a potential role of H. pylori infection in the development of, inter alia , non-alcoholic steatohepatitis, insulin resistance, type 2 diabetes mellitus, colon adenomas and adenocarcinoma, bile ducts cancer, dementia, psoriasis, and chronic utricaria has also been recognised [ 5 , 6 ].…”
Section: Diseases Associated With Helicobacter Pylori mentioning
confidence: 99%
“…In Mogaddam MR et at study both groups (patient and control), 58% were male and 42% were female. The mean age in the patients group was 37.64±16.04 years and in the control group it was 37.55±16.26 years 16 .…”
Section: Discussionmentioning
confidence: 91%